(untitled) (Indian Journal of Nematology, 2024)
The faunistic survey was conducted to determine the status of phytoparasitic nematodes associated with vegetable crops (French bean, cucurbits, tomato, crucifers and potato) under polyhouse conditions. About 81 polyhouses from 52 localities of different districts of Himachal Pradesh were surveyed. Study revealed the presence of different genera of plant parasitic nematodes viz. Meloidogyne sp., Pratylenchus sp., Helicotylenchus sp., Mesocriconema sp., Tylenchorhynchus sp. and Hoplolaimus sp. Out of these nematodes Meloidogyne incognita was predominant with population range (37-2547/200cc soil) followed by Helicotylenchus dihystera (28-838/200cc soil), Pratylenchus coffeae (30-540/200cc soil) and Mesocriconema xenoplax (30-260/200cc soil) respectively. Nematode species were most prevalent in tomato, cucurbits and capsicum. M. incognita was found to be most alarming. The tomato cabbagecowpea and tomato-cucumber-mustard were found to have maximum suppressive effect on M. incognita.